Exploring the immunopathology of type 2 inflammatory airway diseases - AlBloushi, Shaimaa; Al-Ahmad, Mona (Frontiers in Immunology, 2024)
Significant advancements have been achieved in understanding the roles of different immune cells, as well as cytokines and chemokines, in the pathogenesis of eosinophilic airway conditions. This review examines the pathogenesis of Chronic Rhinosinusitis with Nasal Polyps (CRSwNP), marked by complex immune dysregulation, with major contributions from type 2 inflammation and dysfunctional airway epithelium. The presence of eosinophils and the role of T-cell subsets, particularly an imbalance between Treg and Th17 cells, are crucial to the disease's pathogenesis. The review also investigates the pathogenesis of eosinophilic asthma, a unique asthma subtype. It is characterized by inflammation and high eosinophil levels, with eosinophils playing a pivotal role in triggering type 2 inflammation. The immune response involves Th2 cells, eosinophils, and IgE, among others, all activated by genetic and environmental factors. The intricate interplay among these elements, chemokines, and innate lymphoid cells results in airway inflammation and hyper-responsiveness, contributing to the pathogenesis of eosinophilic asthma. Another scope of this review is the pathogenesis of Eosinophilic Granulomatosis with Polyangiitis (EGPA); a complex inflammatory disease that commonly affects the respiratory tract and small to medium-sized blood vessels. It is characterized by elevated eosinophil levels in blood and tissues. The pathogenesis involves the activation of adaptive immune responses by antigens leading to T and B cell activation and eosinophil stimulation, which causes tissue and vessel damage. On the other hand, Allergic Bronchopulmonary Aspergillosis (ABPA) is a hypersensitive response that occurs when the airways become colonized by aspergillus fungus, with the pathogenesis involving activation of Th2 immune responses, production of IgE antibodies, and eosinophilic action leading to bronchial inflammation and subsequent lung damage. This analysis scrutinizes how an imbalanced immune system contributes to these eosinophilic diseases. The understanding derived from this assessment can steer researchers toward designing new potential therapeutic targets for efficient control of these disorders.